Ideas are free : how the idea revolution is liberating people and transforming organizations - Robinson, Alan G. (Berrett-Koehler, 2006)
Based on extensive research with hundreds of companies around the world and in every major field, this practical book shows how to draw the most useful ideas from frontline employees and, in the process, significantly improve the atmosphere--and success quotient--of any organization.